Inside Indonesian Banking: A Multi-Dimensional View of Corporate Governance Performance - Sany Sany; Jordan Hartono; Michelle Susanto (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2025)
The study explores the governance pillar of Environmental, Social, and Governance (ESG) performance of Indonesian banking. Using a mixed method that combines quantitative descriptive analysis with textual triangulation, it provides a more nuanced view of governance practices. Data were drawn from the Refinitiv database as well as the banks sustainability reports and/or annual reports. Six major banks were selected based on availability of consecutive Refinitiv ESG scores from 2018 to 2022, enabling trends analysis. Findings show that the average Governance Pillar Scores was relatively high (74.62), with BBCA.JK scoring the highest and BBTN.JK the lowest over the study period. Among Governance dimensions, the Management Score averaged the highest (83.78), followed by CSR Strategy (63.06) and Shareholder score (54.43). This research contributes to corporate governance literature on Indonesian bank by adopting a mixed-method and applying Refinitiv Governance indicators across Management, Shareholder, and CSR Strategy dimensions. This study also highlights managerial implications, suggesting that banks can strengthen sustainability reporting by enhancing textual disclosure and aligning with Refinitiv ESG frameworks.